On the Judicialization of Health - Ana Santos Rutschman (Washington University Global Studies Law Review, 2019)
The provision of health care has long been at the forefront of domestic and international debates, philosophical inquiries, and political agendas. A growing body of legal scholarship has added to the debate by examining the role of judicial review in the context of health-related litigation. What role, if any, should courts play in compelling the provision of health care or in furthering access to potentially life-saving medicines? This question intersects with multiple strands of the law. For instance, it has an institutional component that interrogates the function(s) of courts within systems of checks and balances. It ties into constitutional design choices, as the right to health is expressly recognized by some national constitutions while others are silent on the matter. And, perhaps more fundamentally, it invites us to revisit our notions of fairness and distributive justice in a world of soaring drug and health care costs. Judge Santos’ timely piece, Beyond Minimalism and Usurpation, richly interweaves constitutional law analysis and empirical data on health-related litigation in Brazil to ponder these issues. Brazil, it should be noted, is not only a country where the right to health is constitutionally protected, but also an epicenter of litigation surrounding socio-economic rights and one of the global leaders in the access to medicines movement. In the Article, Judge Santos proposes that we look beyond what he calls “the American models of judicial activism or minimalism” when reflecting on the role that courts play or should play in interpreting and adjudicating health-related claims. Moreover, Judge Santos suggests that the Brazilian experience in this field might yield lessons that are relevant for other countries in the developing world. In the first half of this response, I have chosen to highlight aspects of the Article that speak to these two prongs, as they carry a special resonance in today’s debates on the provision of health goods and services. But I believe that Judge Santos is too modest in assessing the implications of his work and in connecting some of the topics covered in Beyond Minimalism and Usurpation to phenomena taking place well beyond the developing world. The second half of the response thus turns to parallels between some of the arguments put forth in the Article and selected aspects of health-related litigation in the United States. More broadly, I argue that Judge Santos’ Article advances both scholarship and overall awareness of the phenomenon of judicialization of health, which both encompasses and transcends localized manifestations of judicial review of health-based claims.
Keywords: health law; brazil; judicialization; right to health; health care; healthcare; constitutional law